A study on level of job satisfaction among employees in Sarawak Economic Development Corporation (SEDC) / Frida Jarah David and Nurul Ain Yaakub - David, Frida Jarah; Yaakub, Nurul Ain (2012)
Job Satisfaction has been a construct of study for many researchers in different areas of study and the literature has a multitude of articles. This number has alerted managers and executives to deliberate on the employee’s level of job satisfaction and their behaviour. The search for better jobs and the change of employer became an issue for every organizations as well as Governments. The purpose of this study is to determine the level of job satisfaction, to determine whether there is a significant relationship between job satisfaction and benefit, supervision, and co-workers, to identify the most factor affecting job satisfaction, to determine the influence of demographic factors based on gender, age, education level and monthly income and job satisfaction and to suggest the best strategies by the organization to enhance the job satisfaction of the employees in Sarawak Economic Development Corporation (SEDC). A sample of 100 employees based on simple random sampling was chosen to collect information using a questionnaire. The findings indicated that civil servants were satisfied with their job and statistically positive relationships existed between the dependent variable and the 3 aspects of job satisfaction. The generalization of the results of this study should be cautiously interpreted since the scope of the study is Sarawak Economic Development Corporation (SEDC) civil servants and the variables chosen were benefit, supervision and co-workers. Future studies are recommended so that additional variables can be incorporated.